Trajectory control method of stratospheric airships based on model predictive control in wind field. (February 2019) - Zhang, Jiashi; Yang, Xixiang; Deng, Xiaolong; Lin, Huijing
Trajectory control of the stratospheric airship is an important but challenging task due to the characteristics of large inertia, long time delay, and large disturbance with wind field. Based on six-degrees-of-freedom dynamic model and kinetic model, this paper proposes a model predictive control method for the trajectory control of stratospheric airship in wind field. The aerostatics, aerodynamics, and flight mechanics are incorporated into the model with consideration of wind interference. By linearization of the dynamics equations by small perturbations method, a trajectory controller is designed using model predictive control method. A simulation program is developed from the model and is applied to analyze the control response of the high altitude airship. Results show that the method has a fast response and high accuracy trajectory control in wind field. A simulation comparison of airship performance with model predictive control and traditional sliding mode control shows that model predictive control can give a higher tracking accuracy at initial stage.